2018
DOI: 10.1080/10942912.2018.1505755
|View full text |Cite
|
Sign up to set email alerts
|

Detection of the adulteration in pure cow ghee by electronic nose method (case study: sunflower oil and cow body fat)

Abstract: Cow ghee is very used in some regions of Iran, such as Kermanshah province. Cow ghee is a natural source that contains high-quality nutrients which are needed for the human body. Adulteration in dairy products is not only a serious threat to human health but also it causes economic losses. Diagnosis of foodstuff cheating and its estimation is one of the key concerns in recent years. The aim of this study was the detection of the adulteration in cow ghee by olfactory machine system. Therefore, an electronic nos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(17 citation statements)
references
References 24 publications
1
13
3
Order By: Relevance
“…These results were considerably higher than the results obtained by Ayari et al. (2018a) for detecting adulteration between the animal and edible oil. To evaluate the oxidation of Chinese‐style sausage fat with determination coefficients ( R 2 s), more than .914 and .814 were obtained during processing and storage (Gu, Sun, Tu, & Pan, 2017).…”
Section: Resultscontrasting
confidence: 69%
See 2 more Smart Citations
“…These results were considerably higher than the results obtained by Ayari et al. (2018a) for detecting adulteration between the animal and edible oil. To evaluate the oxidation of Chinese‐style sausage fat with determination coefficients ( R 2 s), more than .914 and .814 were obtained during processing and storage (Gu, Sun, Tu, & Pan, 2017).…”
Section: Resultscontrasting
confidence: 69%
“…Ayari et al. (2018b) also reported similar results regarding the adulteration detection in animal oil and edible oil (Ayari et al., 2018a, 2018b).…”
Section: Resultsmentioning
confidence: 56%
See 1 more Smart Citation
“…Statistical analysis showed that there were significant differences among all the samples. This experiment is in agreement with the work of Jirankalgikar et al [ 12 ] and Ayari et al [ 27 ]. Using more than 10% of vegetable oil adulteration significantly reduced the RM value [ 28 ].…”
Section: Resultssupporting
confidence: 93%
“…As markers of the presence of some substances, VOCs can also be a useful tool for verification in industry (James, Scott, Zulfiqur, & O'Hare, 2005), environmental research (Bieganowski et al, 2018;Guz et al, 2015), medicine (Zhou, Luo, GholamHosseini, Li, & He, 2017), and even in military applications (Patel, 2014). Analyses of VOCs have been widely used to determine the quality of biomaterials (Ayari, Mirzaee-Ghaleh, Rabbani, & Heidarbeigi, 2018;Zhang, Cheng, Ma, & Li, 2017). VOCs were observed in the 1960s as markers of microbial contamination in the case of bacteria, and in the 1970s in the case of fungi (Kamiński, Libbey, Stawicki, & Wąsowicz, 1972).…”
Section: Introductionmentioning
confidence: 99%